2013
DOI: 10.1371/journal.pone.0079523
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive RNA-Seq Expression Analysis of Sensory Ganglia with a Focus on Ion Channels and GPCRs in Trigeminal Ganglia

Abstract: The specific functions of sensory systems depend on the tissue-specific expression of genes that code for molecular sensor proteins that are necessary for stimulus detection and membrane signaling. Using the Next Generation Sequencing technique (RNA-Seq), we analyzed the complete transcriptome of the trigeminal ganglia (TG) and dorsal root ganglia (DRG) of adult mice. Focusing on genes with an expression level higher than 1 FPKM (fragments per kilobase of transcript per million mapped reads), we detected the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 318 publications
(263 reference statements)
8
130
0
1
Order By: Relevance
“…To our knowledge, this report is the first demonstration of UCP1 protein in neuronal mitochondria of a mammal. Earlier reports did not identify UCP1 in mouse TG and DRG (23) and detected only trace amounts of UCP1 transcript in mouse cortex (∼0.01% of UCP1 level in BAT) (21,22), suggesting neuronal UCP1 expression could be a specific feature pertaining to animals that have to withstand prolonged periods of extreme hypothermia.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To our knowledge, this report is the first demonstration of UCP1 protein in neuronal mitochondria of a mammal. Earlier reports did not identify UCP1 in mouse TG and DRG (23) and detected only trace amounts of UCP1 transcript in mouse cortex (∼0.01% of UCP1 level in BAT) (21,22), suggesting neuronal UCP1 expression could be a specific feature pertaining to animals that have to withstand prolonged periods of extreme hypothermia.…”
Section: Discussionmentioning
confidence: 83%
“…It was suggested that this temperatureinduced UCP1 expression in carp may support local cranial endothermy necessary to survive winter dormancy. Trace amounts of UCP1 mRNA have been detected in mouse cortex (21,22), but no expression was observed in peripheral nervous tissues (23).…”
mentioning
confidence: 98%
“…Several -omics approaches have been developed to study pain-related changes in gene expression (7,8) or of proteins (9 -14). Deep-sequencing transcriptomics (RNA-Seq) is able to quantify the majority of the transcriptome (7,8), but only half of mRNA changes account for protein variability (15) limiting the ability to relate results to protein function.…”
mentioning
confidence: 99%
“…Such studies have recently included the profiling of GPCRs expressed in single cells (Manteniotis et al, 2013;Spaethling et al, 2014).…”
Section: Methods and Approaches To Assess Gpcr Expressionmentioning
confidence: 99%
“…Even in such studies, however, one analyzes a population of cells. The use of techniques such as high-resolution RNA sequencing (Manteniotis et al, 2013;Spaethling et al, 2014) and perhaps proteomic methods (Davies et al, 2007;Wu et al, 2012;Eisen et al, 2013) to assess GPCRs in individual cells will thus be an important future direction for defining the profile and variability in GPCR expression in particular cell types. 2) Reproducibility and consistency of methods used to prepare mRNA, cDNA, or protein and to assess gene and protein expression: Standards have been developed to facilitate reproducibility in microarray (Brazma et al, 2001;Hansen et al, 2007;Rung and Brazma, 2013) and proteomic studies (Davies et al, 2007;Taylor et al, 2007), but results from different laboratories can differ.…”
Section: What Are Some Of the Problems And Limitations Of Efforts To mentioning
confidence: 99%